Am I a Technophile? the Narrative Study of Teachers’ Belief about Digital Literacy - Syariful Imam Hadi Cahyono; Nur Arifah Drajati; Ngadiso Ngadiso (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
The aim of the study is to explore teacher’s belief and practice about the use of digital literacy in the EFL classroom. The framework of Borg (2006) about teacher beliefs is used as a theoretical framework for collecting and analyzing data. This study explores how teacher beliefs affect the use digital literacy. The participants of the study were two senior high school teachers in Indonesia. Researchers conducted interviews, classroom observation, and document analysis such as lesson plans, syllabi, and student assignments. The results of the study showed that it was fully crucial to provide a professional development course which was ready-to-use and met the student’s and teacher’s need because in-service teachers have lack of knowledge and experience about digital literacy from their formal learning context. The support of school communities in term of regulation, discussion, sharing experience, and technical aid. Moreover, promoting technology-rich environment also facilitate the use of digital literacy in the classroom in which the technology adopted should be in accordance with digital competence and the needs of students and teachers.